Thrombotic thrombocytopenic purpura associated with dengue and chikungunya virus coinfection: case report during an epidemic period - Bastos, Maria Luiza Almeida; Araújo, Ruth Maria Oliveira de; Oliveira, Deivide de Sousa; Cavalcante, Ana Nery Melo; Silva Junior, Geraldo Bezerra da (Revista do Instituto de Medicina Tropical de São Paulo, 2018)
The present report shows the occurrence of thrombotic thrombocytopenic purpura (TTP) associated with acute dengue and chikungunya virus coinfection, manifesting as a severe disease with high mortality potential. The patient was a 28 year-old man with clinical and epidemiological diagnosis of arboviruses infections who developed thrombocytopenia and anemia, after which oral corticosteroid therapy was started. On the third day of hospitalization, he showed neurological alterations that simulated a cerebral vascular accident, but the imaging examination did not identify ischemic or hemorrhagic alterations. At that moment, the TTP hypothesis was raised so that plasmapheresis and corticosteroid pulse therapy were started, have been essential for the favorable evolution of the case.